The Potential of AI Chatbots as Learning Companions: Early Insights from Students’ Cognitive and Emotional Responses - Adhie Thyo Priandika; Permata Permata (AI and Developmental Insights in Education, 2025)
This study examined the growing educational challenge of understanding how students cognitively and emotionally experience AI chatbots when used as learning companions. Using a convergent mixed-methods design, data were collected from 189 university students through Likert-scale measures of cognitive support, emotional response, and perceived effectiveness, along with 186 written reflections analyzed using thematic analysis. Quantitative results showed strong perceptions of cognitive clarity, positive emotional experiences, and significant associations among the three constructs, indicating that students who felt cognitively supported also viewed the chatbot as more effective. Qualitative themes reinforced these findings by revealing that students valued the chatbot’s step-by-step explanations and experienced a sense of emotional safety when asking questions. Integrated analysis demonstrated convergence across strands, highlighting the intertwined cognitive and emotional dimensions of chatbot-assisted learning. The study contributes early evidence that AI chatbots can function as supportive learning companions with meaningful implications for AI-enhanced education.